Monetary policy and real estate price distortions: How bank lending amplifies housing market imbalances - Vera Baye; Valeriya Dinger (Osnabrück University, Institute of Empirical Economic Research, 2025)
We empirically document deviations of residential real estate prices from fundamental values at the micro level and investigate their relationship with local bank lending growth during a period of unconventional monetary policy. Our findings indicate a positive relationship between credit growth and excessive price increases in real estate markets, with interest rate reductions further amplifying these credit-driven price distortions. Additionally, we provide evidence that banks' search-for-yield behavior explains the increase in lending, particularly among deposit-funded banks that experienced a squeeze of margins during the negative monetary policy rate period. This credit expansion, in turn, directly influences the real economy by fueling local housing markets. In our analysis, we exploit that the introduction of negative monetary policy rates affected banks differently depending on their ex-ante liquidity and relate micro-level real estate data to balance sheet information from locally operating banks and macroeconomic variables.
Keywords: E44; E52; G21; R21; R31; 330; residential real estate prices; housing bubbles; bank lending; search-for-yield; micro data; negative interest rates